International Service Learning among Islamic Higher Education Institution Challenges and Strategies - Sajidin Sajidin; Andang Saehu; Asyraf Isyraqi (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2020)
The study aims at exploring the implementation of International Service Learning (ISL) among Islamic Higher Education Institutions in Indonesia, its challenges, and strategies to cope with them. To explore the phenomena, six Islamic Higher Education Institutions (IHEI) implementing the ISL in Indonesia were purposively selected as sample of the study. A face-to-face interview with the respondents and document analysis towards relevant resources were employed as the main data collection techniques. After analysing the data and, later, triangulated them, the following findings emerge. First, the implementation of ISL was structurally carried out on the basis of preparation, implementation, and evaluation. Second, employing a framework of ISL implementation, coined by Baker-Boosamra, most recommeded steps were followed. Third, ISL among IHEIs encounter some challenges to cope with. Some could be successfully resolved; some others remain unresolved. The study recommends that ISL among IHEIs be properly managed by formulating specific objectives. The formulated objectives serve as the standard of ISL successful implantation.